ANALISIS PENERAPAN E-BUSINESS STUDI KASUS PADA BANK TABUNGAN PENSIUNAN NASIONAL ( BTPN ), TBK - ROYMON PANJAITAN (STEKOM PRESS, 2019)
The application of information technology to support business and various service activities cannot be avoided in the banking industry. The application of e-business in the current era of technology can provide increased profits in transaction services or marketing of banking products, but on the other hand the application of e-business tends to provide losses due to the high cost requirements to operationalize technology. The purpose of this research is to try to do an analysis of the application of e-business in one of the banking industries, namely Bank BTPN, Tbk.The results of the analysis of the application of e-business at Bank BTPN, Tbk is that the application provides many benefits to stakeholders and management. Stakeholders from the customer can easily obtain information and services without having to meet face to face, while the company's internal parties facilitate the company's operational activities, accelerate service and synergize products to increase profits and can continue to be competitive in the midst of the intense competition in the banking business today. In addition to financial benefits, the bank's good image is useful for increasing public trust.